Correlation Between Social Acceptance and Student Self Presentation and Implications in Guidance and Counseling Services - Lia Mita Syahri; Daharnis Daharnis (Jurnal Neo Konseling, 2020)
The task of adolescent social development in peer relations can be said to be successful when there is social acceptance, namely a condition of being accepted or rejected by the social environment. In fact, there are still students who are not accepted by their social environment, such as not having close friends, choosing by themselves in doing various activities and often being ignored. This is presumably due to the students' self-presentation that is not appropriate, so that students cannot present their own picture of their social environment by giving a good impression. The purpose of this study was to describe the conditions of student self-presentation and social acceptance. The population in this study were students of SMAN 7 Padang totaling 648 students and the sample in this study were students of class XI and XII of SMAN 7 Padang, totaling 247 students. Sampling was done by using proportional stratified random sampling technique. The findings of this study are, (1) students' self-presentation is in the high category, (2) social acceptance is in the high category, (3) there is a significant positive relationship between student self-presentation and social acceptance.